Purines. XXXVII. : Synthesis and Reduction of 3, 9-Diallkyladenine Salts Deuterated at the 2-Position : Their Use in the Proton Nuclear Magnetic Resonance Study of Isotopically Unmodified Species - SAITO, Tohru; KIZU, Kyoko; FUJII, Tozo; NAKASAKA, Tsuyoshi (Chem. Pharm. Bull, 1990)
The 2-deuterated species XI-XIII of 3, 9-dimethyladenine salts (Ia, b) and of 3-benzyl-9-methyladenine perchlorate (Ie) have been synthesized from the alkylaminoimidazoles VII and VIII through deuterioformylation with formic-d acid-d, hydrogenolytic demethoxylation, adn amidine-formamido cyclization. Comparison of the proton nuclear magnetic resonance spectra of XI-XIII with those of the isotophically unmodified species Ia, b, e permitted a distinction between C(2)-and C(8)-proton signals observed for a series of 3, 9-dialkyladenine salts (Ia-I) : the C(2)-proton resonates at lower field than does the C(8)-proton by 0.04-0.52 ppm. The low electron density at C(2) of I was also exemplified by the NaBH4 reduction of 3, 9-dimethyladenine perchlorate (Ib) to give the 1, 2-dihydro derivatibe XIX. The structrue of XIX was confirmed by a similar reduction of the 2-deuterated species XII, leading to XX.